Meiotic effects of robertsonian translocations in tuco-tucos of the Ctenomys perrensi superspecies (Rodentia: Ctenomyidae) - Lanzone, Cecilia (2007)
Meiotic behaviour was studied in males of the Ctenomys perrensi superspecies from Argentina that show variations in their chromosome number mostly due to Robertsonian translocations (Rb). A significant positive correlation between cell chiasma frequencies and total chromosome numbers was found. The reduction in chiasma frequency observed in individuals with Rb rearrangements occurred mainly at expenses of proximal and interstitial chiasmata, although significant differences between Rb trivalente and bivalents both in chiasma distribution and univalent frequency were also observed. Nevertheless, not all changes in chiasma distributions could be ascribed to Rb rearrangements. Chromosome synapsis was analysed in Rb hetero- and homozygotes. Trivalente showed a high frequency of synapsis at pericentromeric regions, suggesting no mechanical incompatibilities or delay in the synaptonemal complex formation in such regions. The relationship between chiasma distributions and synaptic patterns is discussed and a hypothesis about the possible role of telocentric or subtelocentric regions in these processes is proposed. It is also concluded that one or two Rb translocations in heterozygosis have weak direct effects on the fertility of the male carriers; therefore C. perrensi superspecies may be prone to maintain Rb chromosomal rearrangements.